A qualitative study on implementer’s perspective of success and challenges: Interactive Popular Theatre (IPT) component of BRAC CST - Nawaz, Shahpara (Brac University, 2023)
This project report is submitted in partial fulfillment of the requirements for the degree of Master of Public Health (MPH), 2023.